예술 경영이 예술가와 예술 작품에 미치는 영향 - 밀레의 「죽음의 신과 나무꾼」을 중심으로 - 안성은(AHN Sung Eun) (프랑스어권 문화예술연구, 2021)
본 연구는 19세기 프랑스에서 화가 밀레를 중심으로 이루어진 예술 경영에 주목하였다. 당시 예술 경영이라는 용어 자체는 존재하지 않았 지만 1859년 밀레의 작품 「죽음의 신과 나무꾼」이 프랑스 국전에서 낙 선하면서, 그 부당함을 알리려는 일련의 움직임은 현대 예술 경영의 과 정인 ‘기획-조직화-지휘-통제’의 단계로 이루어졌다. 『조형예술 잡지』 가 주축이 되어 예술 기관의 역할을 담당하였고, 편집장 샤를 블랑이 예술 경영인의 임무를 수행하였다. 이후 밀레의 위상은 달라졌다. 1860 년 벨기에 화상과 전속 계약을 체결하였고, 1864년 프랑스 국전에서 1 위를 수상하였으며, 1868년에는 레지옹 도뇌르 훈장을 받았다. 따라서 밀레의 예를 통해 예술가와 예술 작품에 있어서 예술 경영의 필요성과 중요성을 확인할 수 있다. When Millet’s Death and the woodcutter was refused at the Salon de 1859, arose an organized and systematic movement in French arts’ community against this unjust happening. Even not being named as ‘art management’, this movement showed the essential elements of arts management. In fact, arts management’s principal functions are recognized in the process of this movement: planning, organizing, supervising and control. During the movement, the role of an art institute was played by Gazette des Beaux-Arts, and that of art manager by Charles Blanc, head of the movement. Charles Blanc planed, organized, supervised and controlled practical tasks of publishing an artistic review on the Salon. He wanted to make public and draw attention on how absurd the refusal of Death and the woodcutter is. He requested Paul Mantz, a Millet expert, of the review to be published on the same page with the print of Death and the woodcutter. It was unprecedented in French art magazine history to publish the refused work’s print, which made a great echo. Not only the artists, but also the writers recognized the aesthetic value of Death and the woodcutter, which embodying The Fables of La Fontaine, and actively showed support to the work of Millet. After this ‘art management’ carried out by Gazette des Beaux-Arts, Millet’s status was shifted up once for all. In 1860, he made a 3-year contract with a Belgian art merchant. It relieved him of pecuniary pressure for the first time in his career. In 1864, he was awarded with the 1st class medal at the Salon, and decorated with the Légion d’honneur in 1868. Millet’s case exemplifies well how necessary and important arts management could be for art works. KCI Citation Count: 0